Casas de sementes comunitárias: estratégia de resistência e manutenção da vida camponesa - Barbosa, Mônica de Moura (2014)
] Experiments storage and seed selection is a very ancient practice dating from the beginning of agriculture, when ancient people began to select and improve seed according to their needs. Over the years, agriculture has undergone many transformations where the seeds came to be genetically modified causing the few peasants were losing their autonomy and food sovereignty. In response to this style flowers Agroecology , understood as a field of knowledge based on a holistic perspective of understanding the phenomena related to food production ( ecological, social and political ) and the discussion of ensuring food sovereignty , in particular the issue of using and preservation of traditional seeds and landraces as opposed aces ' enterprise ' seeds . Contributing to this new way of relating to nature and achievement of autonomy emerge homes Community seed, considered a conservative strategy of maintaining agricultural biodiversity and socio-cultural communities and peoples. This study aimed to understand the houses of seeds are considered strategies of resistance of peasant life against the current model imposed by unsustainable agriculture. Just as understanding the relationships of the peasants (as) with seeds , ways to select , role of women within the homes of seed , cultural aspects and assess whether they constitute conservation of native seeds and know popular tool . The study was conducted in the municipality of Massapê specifically in three communities and one rural settlement which feature homes Community seed. To obtain the data a qualitative -quantitative methodology was used, through interviews and semi-structured questionnaires, participant observation and use of focus group methodology with the research subjects. As results were diagnosed forms of select native seeds that contribute to the maintenance of popular knowledge, the inclusion of women and their struggle for the conquest of space and autonomy. Besides the identification of the subjects from their practices and the relationship of access to land as well as cultural aspects. This sense of community seed houses are configured as a new tool as peasant autonomy, since proposes a new model of development, not only for the field, but for the human population in general.